2023
DOI: 10.1126/sciadv.adf3731
|View full text |Cite
|
Sign up to set email alerts
|

Collective fusion activity determines neurotropism of an en bloc transmitted enveloped virus

Abstract: Measles virus (MeV), which is usually non-neurotropic, sometimes persists in the brain and causes subacute sclerosing panencephalitis (SSPE) several years after acute infection, serving as a model for persistent viral infections. The persisting MeVs have hyperfusogenic mutant fusion (F) proteins that likely enable cell-cell fusion at synapses and “en bloc transmission” between neurons. We here show that during persistence, F protein fusogenicity is generally enhanced by cumulative mutations, yet mutations para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Long-term and chronic neurological manifestations derived from viral neuroinfections are gaining increased attention, especially after the coronavirus disease 2019 (COVID-19) pandemic where long COVID has recently been termed to describe a multitude of symptoms of neurological nature that persist for months after the infection (17) and affect millions of people worldwide (49). To date, the pathophysiological mechanisms associated with the neurological symptoms derived from viral infections are only started to be elucidated, with fusion being a possible mechanism of transmission and spreading (50)(51)(52)(53)(54)(55)(56). Our results indicate that viral infections, driving the expression of viral fusogens, can initiate the irreversible fusion of brain cells, causing alteration in neuronal communication and revealing a possible pathomechanism of neuronal malfunction caused by infection.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term and chronic neurological manifestations derived from viral neuroinfections are gaining increased attention, especially after the coronavirus disease 2019 (COVID-19) pandemic where long COVID has recently been termed to describe a multitude of symptoms of neurological nature that persist for months after the infection (17) and affect millions of people worldwide (49). To date, the pathophysiological mechanisms associated with the neurological symptoms derived from viral infections are only started to be elucidated, with fusion being a possible mechanism of transmission and spreading (50)(51)(52)(53)(54)(55)(56). Our results indicate that viral infections, driving the expression of viral fusogens, can initiate the irreversible fusion of brain cells, causing alteration in neuronal communication and revealing a possible pathomechanism of neuronal malfunction caused by infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are distinct aspects between SMME and SSPE: the shorter time interval between the measles episode or contact with measles and the onset of neurological signs, the lack of intellectual impairment at onset as described in SPPE ( Dyken, 1985 ), the lack of typical SSPE patterns in EEG examination (even though this has only been performed for a few patients with SMME). SPPE patients have MV isolated from CSF with multiple mutations in the M and F proteins, affecting its fusogenic capacity and facilitating the transsynaptic spreading ( Shirogane et al, 2023 ), while we found genetically similar MV in CSF and nasopharyngeal swabs from the SMME patient. Also, as SMME has occurred in severely immunosuppressed HIV individuals, fulminant SSPE has been reported in HIV-infected individuals with good CD4 counts ( Sivadasan et al, 2012 ; Maurya et al, 2016 , Vidhale et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…Some of these ideas have been directly applied to explain the population dynamics of viruses when coinfections occur. For example: deleterious variants can persist for longer when coinfection rates are higher, which is analogous to higher ploidy masking selection on deleterious alleles; different viral variants can coexist stably if coinfections are more productive than single infections (analogous to heterozygote advantage) (Bushman & Antia, 2019; Leeks et al, 2018; Wilke & Novella, 2003); and in meales virus, mutations for cell–cell fusion that are deleterious when combined on the same genome are beneficial when split across multiple co‐transmitting genomes, in an example of viral social interactions reversing the sign of epistasis (Shirogane et al, 2023).…”
Section: Opportunities and Challenges For New Theorymentioning
confidence: 99%
“…From the perspective of virology, evolutionary theory can unify otherwise disparate viral entities, provide new answers to old questions, and offer new directions for empirical research (Díaz‐Muñoz et al, 2017; Domingo‐Calap et al, 2019; Leeks et al, 2021, 2023; Turner & Chao, 1999; Wild et al, 2009; Wilke, 2005). From an evolutionary perspective, viruses represent a new arena for testing existing theory, offer a range of new puzzles to explore, and can both challenge and extend established bodies of theory (Borges et al, 2018; Landsberger et al, 2018; Michalakis & Blanc, 2020; Shirogane et al, 2021, 2023; Sicard et al, 2019; Skums et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation